Elucidation of the mechanism underlying impaired sensorimotor gating in patients with primary blepharospasm using prepulse inhibition - Hao, Xinqing; Huang, Xiaofeng; Yin, Xiaoxue; Wang, Hai-Yang; Lu, Ren; Liang, Zhanhua; Song, Chunli (Frontiers in Neurology, 2023)
Objective We aimed to analyze prepulse inhibition (PPI) impairment of the blink reflex in patients with primary blepharospasm (BSP). Methods We recruited 30 BSP patients and 20 gender- and age-matched healthy controls (HCs). Weak electrical stimulation was applied to the right index finger at interstimulus intervals (ISIs) of 120, 200, and 300 ms before the supraorbital nerve stimulation to investigate PPI size [PPI size = (1 – R2 area at prepulse trials/R2 area at baseline trials) × 100%]. Results The prepulse stimulus significantly inhibited the R2 component at the three ISIs in both groups, but less inhibition was shown in the BSP group (p < 0.05). In HCs, the prepulse stimulus induced prolonged R2 and R2c latencies at the three ISIs and increased the R1 amplitude at ISIs of 120 ms; these changes were absent in BSP patients. In the BSP group, patients with sensory tricks showed better PPI than patients without sensory tricks. Disease duration and motor symptom severity showed no significant correlation with PPI size. Conclusion In BSP patients, PPI was impaired while R1 facilitation was absent. PPI size did not correlate with the motor symptom severity and disease duration. Patients with sensory tricks showed better PPI than those without sensory tricks.